Co-morbidity after oesophageal cancer surgery and recovery of health-related quality of life. Issue 12 (22nd August 2016) - Backemar, L; Wikman, A; Djärv, T; Johar, A; Lagergren, P
Abstract: Background: Although health-related quality of life (HRQoL) recovers after surgery for oesophageal cancer in most long-term survivors, one in seven patients experiences a deterioration in HRQoL for reasons yet unknown. The aim of this study was to assess whether co-morbidities diagnosed after surgery influence recovery of HRQoL. Methods: Patients who underwent surgery for cancer of the oesophagus or gastro-oesophageal junction in Sweden between 2001 and 2005 were included. HRQoL was assessed by means of the European Organization for Research and Treatment of Cancer QLQ-C30 and QLQ-OES18 questionnaires. Repeated-measures ANOVA was used to assess mean differences in HRQoL scores between three co-morbidity status groups (healthy, stable and increased) over time. Probabilities of deterioration in HRQoL were calculated based on marginal probabilities from logistic regression models. Results: At 5 years' follow-up, 153 (24·8 per cent) of 616 patients were alive and 137 responded to at least two of three questionnaires. The healthy and increased co-morbidity groups showed deterioration in almost all aspects of HRQoL at 6 months after surgery compared with baseline. The increased co-morbidity group also deteriorated in several aspects from 3 to 5 years after surgery. Patients with an increase in co-morbidity did not have a significantly increased probability of deterioration in HRQoL over time compared with healthy or stable patients, except with respect to cognitive function, loss of appetite, choking and coughing. Conclusion: Patients with an increase in co-morbidities after oesophagectomy experience long-term deterioration in HRQoL. Abstract : Deterioration in quality of life with increasing comorbidity